Escherichia coli Viability in Coastal Marine Environments: A Case Study - Caruso G; Caruso R (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2015)
Background: The assessment of the bacteriological quality of coastal marine waters through the search of Escherichia coli as an indicator of fecal pollution is a topic of public concern. The context and purpose of the study: During a coastal monitoring program, the abundance and distribution of the actively respiring and dead fraction within the total E. coli population along the Messina coastline (Sicily, Italy) were investigated using a fluorescent-antibody method coupled with the stains 5-cyano-2,3-ditolyl tetrazolium chloride (CTC) or propidium iodide (PI) in order to assess the potential risk related to the viability of this microorganism. Results: This study confirm that the proposed analytical protocols are suitable for E. coli monitoring in seawater, providing in a short time (less than 2 hours from sampling) results comparable to plate count methods currently in use. Main findings: The obtained E. coli counts showed spatial and temporal variations - although not significant - in the percentage of CTC+ cells, suggesting that some cells were still retaining their viability properties, and their abundance was affected by the presence of streams and by the hydrodynamic regimen of the Messina Straits. Conclusions: This study is a contribution to the knowledge of the distribution and viability properties of E. coli present in the waters of Messina coastline in terms of its active and dead components. Brief summary: The cell viability assay through fluorescent antibody and viability dyes offers an interesting research perspective, with important implications for a more reliable estimate of the bacteriological quality of seawater. Any potential implications: The determination of the different physiological states coexisting within the E. coli population is of great significance for human health protection, since it may provide information on the effective risk played by the living component of this microorganism.